Influence of competition and intraguild predation between two candidate biocontrol parasitoids on their potential impact against Harrisia cactus mealybug, Hypogeococcus sp. (Hemiptera: Pseudococcidae) - Aguirre, María Belén (2021)
When two or more parasitoid species, particularly candidates for biocontrol, share the same target in the same temporal window, a complex of behaviors can occur among them. We studied the type of interactions (competition and intraguild predation) that existed between the nymphal parasitoids Anagyrus cachamai and A. lapachosus (Hymenoptera: Encyrtidae), two candidate neoclassical biocontrol agents against the Puerto Rican cactus pest mealybug, Hypogeococcus sp. (Hemiptera: Pseudococcidae). The surrogate native congener host in Argentina, the cactus mealybug Hypogeococcus sp., was studied to predict which species should be released; in the case that both should be released, in which order, and their potential impact on host suppression. In the laboratory we conducted experiments where different densities of the host mealybug were exposed to naive females of A. cachamai and A. lapachosus sequentially in both directions. Experiments were analyzed by combining a series of competitive behavioral and functional response models. A fully Bayesian approach was used to select the best explaining models and calculate their parameters. Intraguild predation existed between A. cachamai, the species that had the greatest ability to exploit the resource, and A. lapachosus, the strongest species in the interference competition. The role that intraguild predation played in suppression of Hypogeococcus sp. indicated that a multiple release strategy for the two biocontrol agents would produce better control than a single release; as for the release order, A. lapachosus should be released first.